IN STENT RESTENOSIS (ISR) IN PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION (PCI) FOR CORONARY ARTERY DISEASE (CAD) - ULLAH , S; ARSHAD , MH; HUSSAIN , J (Biological and Clinical Sciences Research Journal, 2024)
In-stent restenosis (ISR) remains a significant clinical challenge in patients undergoing percutaneous coronary intervention (PCI) for coronary artery disease (CAD). Objectives: The main aim of the study is to find the In-Stent Restenosis (ISR) in patients undergoing percutaneous coronary intervention (PCI) for coronary artery disease (CAD). Methods: This cross-sectional study was conducted at Prime Teaching Hospital Peshawar from January 2023 till December 2023. Data were collected from 80 patients from both genders. Patients who underwent PCI for CAD and developed ISR, as confirmed by angiographic or intravascular imaging studies, were included. Data were collected in a systematically designed performance. Information was collected from electronic medical records, angiographic reports, and procedural databases. Results: Data were collected from 80 patients according to inclusion criteria. The mean age of the patients was 65.09±8.5 years. There were 52 (65%) male and 48 (35%) female patients. Hypertension was present in 60 (75%), dyslipidemia in 48(60%) and DM in 36 (45%) patients. There was a significant association between older age and increased likelihood of ISR development post-PCI (Mean age ISR: 68.01 ± 7.2 years vs. No ISR: 62.39 ± 9.1 years, p=0.02). However, gender did not significantly influence ISR occurrence (71% male ISR vs. 62% male No ISR, p=0.42). Conclusion: It is concluded that ISR represents a significant challenge in patients post-PCI for CAD, with a substantial incidence observed in this study. Older age, diabetes mellitus, and DES implantation were identified as essential contributors to ISR development.